Epigenetic regulation in coronary artery disease: from mechanisms to emerging therapies - Gao, Rui; Liu, Meilin; Yang, Haoyi; Shen, Yuhan; Xia, Ni (Frontiers in Molecular Biosciences, 2025)
Atherosclerosis, the primary cause of coronary artery disease (CAD), remains a leading global cause of mortality. It is characterized by the accumulation of cholesterol-rich plaques and inflammation, which narrow the coronary arteries and increase the risk of rupture. To elucidate this complex biological process and improve therapeutic strategies, CAD has been extensively explored from an epigenetic perspective over the past two decades. Epigenetics is a field investigating heritable alterations in gene expression without DNA sequence changes, such as DNA methylation, histone modifications, and non-coding RNAs. Increasing evidence has indicated that the development of CAD is significantly influenced by epigenetic changes. Meanwhile, the impact of epigenetics in CAD is now transitioning from pathophysiology to therapeutics. Focusing on the key epigenetic enzymes and their target genes will help to facilitate the diagnosis and treatment of CAD. This review synthesizes novel epigenetic insights into CAD, addressing the pathological processes, key molecular mechanisms, and potential biomarkers. Furthermore, we discuss emerging therapeutic strategies targeting epigenetic pathways. By focusing on pivotal enzymes and their associated genes, this work aims to advance CAD diagnostics and interventions.